2022
DOI: 10.1038/s41467-022-28244-5
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas9 induces large structural variants at on-target and off-target sites in vivo that segregate across generations

Abstract: CRISPR-Cas9 genome editing has potential to cure diseases without current treatments, but therapies must be safe. Here we show that CRISPR-Cas9 editing can introduce unintended mutations in vivo, which are passed on to the next generation. By editing fertilized zebrafish eggs using four guide RNAs selected for off-target activity in vitro, followed by long-read sequencing of DNA from >1100 larvae, juvenile and adult fish across two generations, we find that structural variants (SVs), i.e., insertions and de… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 57 publications
1
65
0
Order By: Relevance
“…For our PCSK9 sgRNA design, in silico off-target analysis showed no potential off-target sites with less than four mismatched nucleotides and only 21 potential off-target sites with four mismatches, highlighting the high degree of specificity of our design. On the other hand, we did not detect any large structural variations at the edited PCSK9 locus in our work, contrarily to previous observations for direct ribonucleoprotein (RNP) delivery (Höijer et al, 2022). This might be due to the lower amount of RNPs delivered by the engineered EVs, suggesting that EV-based delivery could have a potential advantage compared to other vehicles in circumventing the unwanted effects often observed with CRISPR/Cas9.…”
Section:  Discussionsupporting
confidence: 60%
“…For our PCSK9 sgRNA design, in silico off-target analysis showed no potential off-target sites with less than four mismatched nucleotides and only 21 potential off-target sites with four mismatches, highlighting the high degree of specificity of our design. On the other hand, we did not detect any large structural variations at the edited PCSK9 locus in our work, contrarily to previous observations for direct ribonucleoprotein (RNP) delivery (Höijer et al, 2022). This might be due to the lower amount of RNPs delivered by the engineered EVs, suggesting that EV-based delivery could have a potential advantage compared to other vehicles in circumventing the unwanted effects often observed with CRISPR/Cas9.…”
Section:  Discussionsupporting
confidence: 60%
“…In terms of mutation types (Figure 3C ) and homology at the junctions (Figure 3E ), the two sequence methods generate comparable footprints, with the exception of deletions with insertions (delins), which are more frequently found in PacBio data (Figure 3C ). While the additional mutations detected in PacBio versus Illumina sequencing on these CRISPR sites in mES cells may appear relatively modest, research has shown that such large deletions may occur more frequently in certain cell types and species and that long-read sequencing provides a powerful method to detect undesired genome modifications ( 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Recent technological advances in CRISPR/Cas systems are making it possible to induce nucleotide substitutions of interest in a target gene (a technique named ‘allele replacement’) and chromosomal rearrangements [ 104 , 105 ], as reviewed by Ansai and Kitano [ 104 ] in this issue. Although these genome editing technologies often have off-target effects [ 106 ], we should eventually be able to remove such undesirable mutations by backcrossing or future technological advances.…”
Section: How To Go Beyond Candidate Loci To Identify Causative Genes ...mentioning
confidence: 99%